Selectivity of pre-and post-emergence herbicides to very-early maturing soybean cultivars - Fornazza, Felipe Guilherme Ferreira; Constantin, Jamil; Machado, Fellipe Goulart; Oliveira Jr., Rubem Silvério de; da Silva, Gustavo Delabio; Rios, Fabiano Aparecido (Comunicata Scientiae, 2019)
The combination of pre- and post-emergence herbicides may affect their selectivity to soybean plants, especially to short-cycle cultivars. The objective of this work was to evaluate the selectivity of pre- and post-emergence herbicides to very-early maturing soybean cultivars. Two field experiments were conducted, one in Mandaguaçu, Paraná (E1) and other in Rio Verde, Goiás (E2), Brazil, using a 4×7 factorial arrangement. The treatments consisted of four pre-emergence herbicide managements (S-metolachlor at 1440 g ha-1, diclosulam at 25.2 g ha-1, sulfentrazone at 300 g ha-1, and no herbicide application); and seven post-emergence herbicide managements (lactofen at 120 g ha-1, chlorimuron-ethyl at 12.5 g ha-1, bentazon at 720 g ha-1, lactofen at 120 g ha-1 + chlorimuron-ethyl at 12.5 g ha-1, glyphosate at 900 g a. e. ha-1, two sequential glyphosate applications at 720 g a. e. ha-1 each, and no herbicide application). The early-maturing soybean cultivars evaluated showed sensitivity to the herbicides used. The combined use of pre- and post-emergence herbicides increased the occurrence of injuries in the plants. Diclosulam and sulfentrazone were the least selective pre-emergence herbicides. All herbicide combinations used affected soybean grain yield in E1; lactofen, chlorimuron, and bentazon presented the least selectivity in E2.